The Role of Local Cuisine in Promoting Culinary Tourism in Tongging Village, Merek District, Karo Regency, North Sumatera - Ginting, Loli Gunali; Lingga, Anisa Putrisari (Sekolah Pascasarjana Universitas Brawijaya, 2023)
This study qualitatively explores the perspectives of Tongging Village's local community, especially those engaged in tourism and government, concerning the promotion of indigenous culinary tourism. The research involves figures like Rumondang Malai, owner of Lahi Jaya; Yogi, from Permata Tongging; Vina, an employee at Vhi Vhi; Samsudin, owner of Suroboyo; and an interview with Ms. Rista Natalia Sinaga, the economic sector head, enriching the study. Methods encompass observation, interviews, and documentation. Findings reveal unanimous agreement among tourism stakeholders about integrating local cuisine as a cornerstone of Tongging's culinary tourism. Unique to the area, this cuisine holds allure and visitor-drawing potential. Tourism stakeholders express eagerness to partake in government-led initiatives, underscoring the need for public-private cooperation. They advocate for infrastructure development, including a theme park, to captivate visitors and steer them toward local eateries. Maintained roads are deemed crucial for accessibility. Additionally, stakeholders propose financial aid for culinary businesses, aiding in capital and marketing. This strategic focus on the creative economy promises to elevate Tongging Village's gastronomic appeal, enhancing its overall tourism experience. Keywords: local culinary, tourism, tongging village